JAPANESE CONSUMERSâ BEHAVIORAL INTENTION AND VALUES TOWARD FUROSHIKI AS A PACKAGING FOR FOOD PRODUCTS - Jessica, Alia
Japan has been facing the problem of over packaging because the products in Japan are using excessive packaging materials, especially paper and plastic based packaging. One of the ways to alleviate the problem of excessive waste is to use a more environmentally friendly packaging material such as Furoshiki. In that sense, this study would like to analyze the Japanese packaged food consumers’ behavioral intention toward Furoshiki and compare the result with their behavioral intention toward paper and plastic based packaging using the Extended Fishbein model. Furthermore, this study will also explore the Japanese packaged food consumers’ values using Kahle’s List of Values as an additional evaluation factor to measure their behavior. From the Extended Fishbein model calculation, the behavioral intention of the Japanese consumers’ toward purchasing Furoshiki as a packaging for food products scored the highest compared to paper and plastic packaging. From Kahle’s List of Values, it can be identified that the values that the majority of Japanese consumers in this research chose warm relationships with others, self-fulfillment, and fun and enjoyment of life as the most important value to have in life.